Analysis of students’ perceptions on the Freedom of Learning - Independent Campus (MBKM) program at Chemistry study program of Ma Chung University - Yuyun Yuniati; Lilis Lestari Wilujeng (Jurnal Penelitian dan Evaluasi Pendidikan, 2023)
Considering that Indonesian education has gone through such a long journey from 1922 to 2022 now, it is necessary to have an educational program that is able to meet the demands of workers' needs in this era of globalization. In the end, the Directorate General of Higher Education, Research, and Technology designed an education policy system in the realm of higher education, namely "Freedom of Learning - Independent Campus", as an accurate strategy for optimizing academics in today's Indonesia. In this study, a survey was aimed at 40 undergraduate students of the Chemistry Study Program at Ma Chung University. Data analysis were made by quantitative approach of the nine questions succcessfully answered by students who filled out questionnaires in the online multiple choice questionnaire with a dependency test by nonparametric statistical methods. As a result, the majority of students of the Chemistry Study Program were quite enthusiastic about this new educational policy, although it was necessary to optimize all internal strategies of the study program curriculum, so that it could be in accordance with the activities designed in the "Freedom of Learning - Independent Campus" Program.